4(a+12)+5(8)=

Simple and best practice solution for 4(a+12)+5(8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(a+12)+5(8)= equation:


Simplifying
4(a + 12) + 5(8) = 0

Reorder the terms:
4(12 + a) + 5(8) = 0
(12 * 4 + a * 4) + 5(8) = 0
(48 + 4a) + 5(8) = 0

Multiply 5 * 8
48 + 4a + 40 = 0

Reorder the terms:
48 + 40 + 4a = 0

Combine like terms: 48 + 40 = 88
88 + 4a = 0

Solving
88 + 4a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-88' to each side of the equation.
88 + -88 + 4a = 0 + -88

Combine like terms: 88 + -88 = 0
0 + 4a = 0 + -88
4a = 0 + -88

Combine like terms: 0 + -88 = -88
4a = -88

Divide each side by '4'.
a = -22

Simplifying
a = -22

See similar equations:

| 3/4t-5.8 | | 12x-2=3x+14 | | -2n^2+15n-13=0 | | 154=x^2+15x | | -4y-12x=4 | | 2n^2+15n-13=0 | | 0.4*x=75000 | | a-32=29 | | 3x+14=-82 | | 4x^2-50x+486=0 | | t=16t^2+3136 | | X/2-8=6 | | 7.9+d=12 | | 12x-2=-3x+14 | | 2cos^2x+5cosx+5=0 | | -7-5x=-22 | | 6(1-x)+5=2x+3 | | -x-8+7= | | (x-4)(2x+5)= | | (5+3x)-(10x-15)=-22 | | (5+3x)-(10a-15)=-22 | | 26=g | | 6^9-x=1/36 | | 7-3+5x(6-2)= | | 7x^2-4x-6=0 | | h/-1.05=-o.36 | | -48a+8a=-48 | | t=1x+2 | | 4x^2-y^2-48x+140=0 | | 12x^4-8x+4x^2-3= | | 3x+8=8x-13 | | -4(-p-7)-2(5p-4)=12 |

Equations solver categories